Effect of Raw Material and Process Conditions During the Dry Forming of CTMP Fibers for Molded Pulp Products - Eva Pasquier; Kathrin Mörseburg; Kristin Syverud; Jost Ruwoldt (Journal of Natural Fibers)
This article provides a concise insight into the thermoforming of airlaid CTMP pulp. First, the airlaid process was studied, showing that fiber fractionation and the retention of fines occurred in the forming head. Then, the effect of temperature and pressure during thermoforming was investigated. Harsher conditions, i.e. higher temperature and pressure, yielded greater densification of the substrate and higher tensile strength. The maximum strength was found at the highest settings tested, that is, 100 MPa and 200°C. The screening of thermoforming conditions was also compared to previously published results on wetforming. Next, the effect of softwood CTMP pulp was delineated, which on average showed the best mechanical properties at elevated freeness and high degrees of bleaching. At last, a comparison between dry forming and wetforming was made for one selected pulp quality. Here, the dryformed substrates were stiffer at low elongation, yet the wetformed substrates yielded a greater extensibility and higher tensile strength. In conclusion, dryformed pulp mostly relies on temperature and pressure for bond formation during thermoforming, which produces materials that are distinctly different from wetformed molded pulp.